A construção de uma performance da obra para piano de Guilherme Nascimento (1970): a interação entre intérprete e compositor - André Barbosa dos Santos (2020)
The present dissertation had as objective to research the construction of a performance of the work for piano of the composer Guilherme Nascimento (1970), through the interaction between interpreter and the composer. So far, his piano work consists of three compositions: Os abacaxis não voam [The pineapple does not fly] (2001), Eu só fico louco quando o vento sopra de nor-noroeste [I only goes crazy when the wind blows from the northwest] (2005) e Que doce som de prata faz a língua dos amantes à noite [What a sweet sound of silver makes the tongue of lovers at night] (2008). The research was structured in three parts: biographical survey, study of the compositions using exclusively the score and, finally, the interaction with the composer through interviews, dialogues and performances of the works in his presence. This process led us to understand in a deeper and clearer way about the intentions and ideas of the composer in relation to his work with regard to technical, interpretive and creative aspects.